Limitation of dynamic power parameters in transitional processes - Sokolenko, Anatoly; Shevchenko, Oleksandr; Stepanets, Oleg; Romanchenko, Natalia; Shevchenko, Anastasiia (My University, 2020)
The article is devoted to the analysis of the prospects of the complex use of the accumulated potential energy on the example of a mechanism for lifting, horizontal movement and loading of cargoes, for example, in transport container with limitation of dynamic loads. On the basis of the analysis of the peculiarities of the shock loads in two-mass systems, the possibility of using the rigidity of the springy pendant as a variable factor to achieve the given relations between static and dynamic loads during their course in the gravitational field was determined.
Keywords: dynamics; rigidity; deformation; mass; loading; кафедра мехатроніки та пакувальної техніки; кафедра процесів і апаратів харчових виробництв; кафедра технології хлібопекарських і кондитерських виробів